Relationship between Short Term Memory and Cardiopulmonary Fitness of Administrative Officers at Universitas Padjadjaran - Iswaran Ampalakan; Ambrosius Purba; Sunaryo Barki Sastradimaja (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: The work of administrative officers depends a lot on their capability in memorizing. Increased fitness is strongly associated with a better memory. This study was conducted to determine the relationship between cardiopulmonary fitness and short term memory.Methods: This analytical cross sectional study was carried out from August to September 2014. Subjects from administrative offices within Universitas Padjadjaran were chosen by simple random sampling. 101 individuals were selected, comprising of 68 males and 33 females. Data were obtained through Digit Span Test for short term memory and the cardiopulmonary fitness was measured using Harvard Step Test. The VO2 Max obtained was correlated with the Digit Span Test score.Results: The mean for cardiopulmonary fitness of males was found to be 36.1, with standard deviation 8.63, whereas mean cardiopulmonary fitness for females was found to be 32.94, with standard deviation 7.5. For correlation analysis, the result of Spearman’s rank analysis from the study showed that the p-value is 0.00. Comparing to the significance level α=5%, the p value is worth less, thus the null hypothesis, Ho is rejected. Therefore, it could be concluded that there was a relationship between cardiopulmonary fitness and short term memory of male and female administrative officers at Universitas Padjadjaran.Conclusions: There is a relationship between cardiopulmonary fitness and short term memory of male and female administrative officers at Universitas Padjadjaran. [AMJ.2016;3(1):34–7] DOI: 10.15850/amj.v3n1.693